2018
DOI: 10.1089/pancan.2018.0005
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Adenocarcinoma in a Patient with Partial Intestinal Malrotation

Abstract: Background: Small bowel cancers, specifically duodenal cancer, occur at very low rates but require aggressive surgical resection when diagnosed. An even rarer finding is the presence of intestinal malrotation.Case Presentation: We present the unique case of a patient with both duodenal cancer and partial intestinal malrotation undergoing pancreaticoduodenectomy. We discuss the challenges faced and techniques used to successfully perform a surgical resection in this circumstance.Conclusion: Understanding of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Malrotation is a congenital intestinal gestational disorder that affects not only the positioning of the midgut but also its vascular supply, and sometimes the ligament of Treitz is in abnormal position or even absent. It is generally a disease of childhood, but it can have significant implications later in adult surgeries as well, and sometimes it can cause recurrent abdominal pain and volvulus [ 6 – 8 ], but it rarely presents with a gastrointestinal neoplasm [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malrotation is a congenital intestinal gestational disorder that affects not only the positioning of the midgut but also its vascular supply, and sometimes the ligament of Treitz is in abnormal position or even absent. It is generally a disease of childhood, but it can have significant implications later in adult surgeries as well, and sometimes it can cause recurrent abdominal pain and volvulus [ 6 – 8 ], but it rarely presents with a gastrointestinal neoplasm [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…These relations need to be studied in detail preoperatively on the imaging studies to avoid such intraoperative difficulties. 2 3 11…”
Section: Discussionmentioning
confidence: 99%
“…Also, the anastomosis will be paracolic and mobilization of hepatic flexure and cecum may be avoided in these cases. 2 3 5 11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no report on the reconstruction procedure was found. We conducted a review of literature that included Japanese studies by searching the PubMed database, and we found reports on a total of 16 patients with intestinal malrotation who underwent pancreaticoduodenectomy (Table 1) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. None of the 16 patients developed any complication associated with reconstruction.…”
Section: Discussionmentioning
confidence: 99%